2021
DOI: 10.1017/s0003055420001070
|View full text |Cite
|
Sign up to set email alerts
|

When Are Legislators Responsive to Ethnic Minorities? Testing the Role of Electoral Incentives and Candidate Selection for Mitigating Ethnocentric Responsiveness

Abstract: Previous studies have documented ethnic/racial bias in politicians’ constituency service, but less is known about the circumstances under which such ethnocentric responsiveness is curbed. We propose and test two hypotheses in this regard: the electoral incentives hypothesis, predicting that incentives for (re)election crowd out politicians’ potential biases, and the candidate selection hypothesis, stipulating that minority constituents can identify responsive legislators by using candidates’ partisan affiliati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 39 publications
(51 reference statements)
0
12
0
Order By: Relevance
“…Black legislators, however, were significantly more likely to respond to the inquiry regardless of whether or not the letter came from a constituent, suggesting intrinsic motivations outside electoral politics may guide politicians' representation of minority interests. In a recent study, Danish local incumbent politicians were found to be less responsive to requests for information on where to vote in an upcoming election from an individual from a minority (i.e., Middle Eastern/North African) background (Dinesen et al, 2021). Whether or not the letter writer signaled their intention to vote for the politician did not significantly increase politicians' responsiveness.…”
Section: Politicians' Motives To Support Minority Interestsmentioning
confidence: 88%
See 3 more Smart Citations
“…Black legislators, however, were significantly more likely to respond to the inquiry regardless of whether or not the letter came from a constituent, suggesting intrinsic motivations outside electoral politics may guide politicians' representation of minority interests. In a recent study, Danish local incumbent politicians were found to be less responsive to requests for information on where to vote in an upcoming election from an individual from a minority (i.e., Middle Eastern/North African) background (Dinesen et al, 2021). Whether or not the letter writer signaled their intention to vote for the politician did not significantly increase politicians' responsiveness.…”
Section: Politicians' Motives To Support Minority Interestsmentioning
confidence: 88%
“…Politicians' recognition of the needs of others can be an important precursor to political representation. Still, research shows that politicians may discount the needs of those from minority backgrounds, focusing attention on issues that align with their own priorities and preferences (Butler et al, 2011;Butler, 2014;Dinesen et al, 2021). Nonetheless some politicians do continue to advocate for the needs of under-served communities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The version of Dinesen et al 2021 that originally published online was not the final version. The article has now been updated.…”
mentioning
confidence: 99%